Pengaruh Kemandirian Keuangan Dan Belanja Modal Terhadap Kinerja Keuangan Dengan Pertumbuhan Ekonomi Sebagai Variabel Moderasi - Mahardika Burhan; Kartini Kartini; Darwis Said (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to examine and analyze the effect of financial independence and capital expenditure on financial performance with economic growth as the moderating variable. The population in this study is the district/city of South Sulawesi Province as many as 24 districts/cities with the observation year 2016 to 2020. This type of sample uses a saturated sample where the population is the sample. The data was processed using the panel data regression statistical test method. The results of this study indicate that: First, financial independence has a positive and significant effect on the financial performance of local governments. Second, capital expenditure has a significant positive effect on the financial performance of local governments. Third, economic growth strengthens in moderating self-reliance on regional financial performance. Fourth, economic growth strengthens capital expenditures on the government's financial performance in the districts/cities of South Sulawesi Province.